Mayor KNIL Oerip Soemohardjo dan Sejarah Kebijakan Awal Pembentukan Tentara Nasional Indonesia - ENDRO TRI SUSDARWONO (ISTORIA: Jurnal Pendidikan dan Sejarah, 2020)
Oerip Soemohardjo was appointed second lieutenant (KNIL) on October 24, 1914 with the staamboek number 77352 contained in the Sinar Djawa daily edition of October 24, 1914, having previously graduated from the Jakarta Inlandsche Officiern School. Oerip was classified as an officer respected by all groups while serving in the KNIL. During 24 years of serving in the KNIL Oerip actually almost held the rank of Lieutenant Colonel before retiring. On October 5, 1945 BKR (People's Security Agency) forces were made TKR (People's Security Army). It was to organize the TKR that the Government, which at that time was still domiciled in Jakarta, summoned Mr. Oerip, who lived as a retired Major of KNIL near Yogyakarta. Pak Oerip obtained a mandate from the Government as the Chief of General Staff to organize TKR. Lt. Gen. Oerip Soemohardjo on 12 November 1945 summoned all Division Commander and TKR regiments to attend a meeting in Yogyakarta, the new seat of the TKR Headquarters, after Jakarta was occupied by Allied troops. The main event was the election of the Great Commander. The conference was chaired by the Chief of General Staff Lt. Gen. Oerip Soemohardjo and proceeded smoothly, but then a tense atmosphere emerged when it was announced about an urgency that could not be postponed, forced to hold an additional meeting agenda, which was to determine / choose the candidates to be elected as the Supreme TKR Leaders